Educación y globalización: una visión crítica. (2016)
This article addresses a subject of full force for education: the relationship between education and globalization from a critical perspective. It explores and analyzes the role of schools against globalization and the demands it entails. To achieve this goal, various sources of information were consulted and they allowed first to define the nature and scope of globalization as discourse and process; and second, to explore the relationship between globalization and education, the demands and the impact from a critical paradigm; because this emphasizes the need to transform schools into true spaces of political socialization that address the negative effects of globalization and demonstrations of power that are woven into it.